Effects of two submerged macrophyte species on microbes and metazoans in rooftop water-storage ponds with different labile carbon loadings. (1st March 2022) - Maceda-Veiga, Alberto; MacNally, Ralph; Rodríguez, Sara; Szabo, Sandor; Peeters, Edwin T.H.M.; Ruff, Thomas; Salvadó, Humbert
Highlights: C. demersum may be a cost-effective option in the rooftop-water treatment process. C. demersum was superior to E. densa at oxygenating and reducing water conductivity and water turbidity. E. densa was better at reducing water chlorophyll-a but significantly increased the amount of filamentous bacteria. The two macrophyte treatments did not differ in the amount of detritus accumulated. C. demersum had the more diverse taxon indicator community of algae and protozoa. Abstract: Nature-based solutions including rooftop-water storage ponds are increasingly adopted in cities as new eco-designs to address climate change issues, such as water scarcity and storm-water runoff. Macrophytes may be valuable additions for treating stored rooftop waters and provisioning other services, including aquaponics, esthetic and wildlife-conservation values. However, the efficacy of macrophyte treatments has not been tested with influxes of different labile carbon loadings such as those occurring in storms. Moreover, little is known about how macrophytes affect communities of metazoans and microbes, including protozoans, which are key players in the water-treatment process. Here, we experimentally investigated the effectiveness of two widely distributed macrophytes, Ceratophyllum demersum and Egeria densa, for treating drained rooftop water fed with two types of leaf litter, namely Quercus robur (high C lability) and Quercus rubra (low C lability). C. demersum was better than E. densa at reducing water conductivity (by 10 ̶ 40 µS/cm), TDS (by 10–18 mg/L), DOC (by 4–5 mg/L) and at increasing water transparency (by 4–9%), water O2 levels (by 19–27%) and daylight pH (by 0.9–1.3) compared to leaf-litter only microcosms after 30 days. Each treatment developed a different community of algae, protozoa and metazoa. Greater plant mass and epiphytic chlorophyll-a suggested that C. demersum was better at providing supporting habitat than E. densa . The two macrophytes did not differ in detritus accumulation, but E. densa was more prone to develop filamentous bacteria, which cause sludge bulking in water-treatment systems. Our study highlights the superior capacity of C. demersum and the usefulness of whole-ecosystem experiments in choosing the most adequate macrophyte species for nature-based engineered solutions. Graphical abstract: Image, graphical abstract